1966
DOI: 10.1002/j.1537-2197.1966.tb07331.x
|View full text |Cite
|
Sign up to set email alerts
|

Cine‐photomicrography of Low Temperature Effects on Cytoplasmic Streaming, Nucleolar Activity and Mitosis in Single Tobacco Cells in Microculture

Abstract: Living, unstained, single tobacco (Nicoliana tabacum × N. glutinosa) cells (clone H‐196) were grown in microcultures in liquid medium containing sucrose, mineral salts, coconut milk and 2,4‐dichlorophenoxyaeetic acid. Time‐lapse motion pictures were taken through interference and phase microscopes. The movement of cytoplasm and cell organelles gradually slowed and ultimately completely ceased as the cell was cooled by dry ice. The cessation of the movement of cell organelles took place between 5 and –7C. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

1970
1970
1987
1987

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…For example, protoplasmic streaming rapidly ceases (LEWIS 1956) or is greatly reduced (PATTERSON and GRAHAM 1977) at temperatures around 10 to 12°C in chilling-sensitive species and is associated with altered cytoplasmic morphology such as thinning of transvacuolar strands and the formation of numerous small vesicles (DAS et al 1966) which occur within seconds (PATTERSON et al 1980).…”
Section: Cellular Manifestationsmentioning
confidence: 98%
“…For example, protoplasmic streaming rapidly ceases (LEWIS 1956) or is greatly reduced (PATTERSON and GRAHAM 1977) at temperatures around 10 to 12°C in chilling-sensitive species and is associated with altered cytoplasmic morphology such as thinning of transvacuolar strands and the formation of numerous small vesicles (DAS et al 1966) which occur within seconds (PATTERSON et al 1980).…”
Section: Cellular Manifestationsmentioning
confidence: 98%
“…et al (1) have reported a number of cytoplasmic changes during cooling in tobacco cells in the range of 5 to -7 C. Tilney and Porter (9) reported the disappearance of microtubules from the axopodia of a protozoan and formation of short tubules as a disintegration product at a temperature of 4 C. Sieve tubes contain various fibrillar structures known as P-protein. It may be that these structures, like those discussed above, disintegrate or undergo a change in form at low temperatures, leading to an increased resistance to flow through the sieve tubes.…”
mentioning
confidence: 99%
“…Squash preparations of root tips ordinarily show the nucleoli which have uniformly in termingled contents with some vacuolar inclusions, and a distinct encircling light zone called the "nucleolar halo" (Kordan 1964, Das et al 1966), (Fig. 2a).…”
Section: Resultsmentioning
confidence: 99%